A CASE STUDY OF SIMULATING VARIOUS NUMBER OF GATE POSITIONS AND THEIR IMPACT THROUGH T-RTM TECHNOLOGY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The study presented aims to investigate the influence from different gate positioning on the final product in T-RTM technology. The research is done using the specialized Moldex3D software. The studies conducted found that the symmetrical arrangement of injection ports and the approach to progressive injection with reduced pressure on the secondary gates result in significantly better deformation outcomes, with values close to 95% better compared to the deformation results in the approach with simultaneously open ports.